Desarrollo de hibridos de Brachiaria resistentes a cuatro especies de salivazo (Homoptera: Cercopidae) - sotelo, G.=700 1 Cardona M, C.; Miles, J.
(Es, En)
Ilus., 19 ref.
Keywords: BRACHIARIA DECUMBENS; BRACHIARIA BRIZANTHA; PLAGAS DE PLANTAS; AENEOLAMIA VARIA; ZULIA (INSECTO); RESISTENCIA GENETICA; COLOMBIA; SALIVAZO; MION DE LOS PASTOS